IMPORTÂNCIA DA PRODUÇÃO PRIMÁRIA NO RETORNO DO ICMS NOS MUNICÍPIOS DO VALE DO TAQUARI/RS - Adalberto Schnorrenberger (Universidade Federal do Maranhão, 2014)
The current essay aimed to estimate primary production in The Taquari Valley cities and investigate its relevance for the financial return through resource transfers of State Tax for Goods and Services - ICMS - by the State Government. In order to carry out the research data were collected from the city’s reports as well as from reports published by The Farm Secretary of RS - SEFAZ. Results show that ICMS is one of the main sources of revenue for the Taquari Valley cities and it is connected to the capacity of aggregated value generation of economical activities among them primary production is essential. Notes that this activity is considerably relevant for the ICMS distribution criteria, the development of public policies promoting such activity is suggested in order to extend city tax collection so that it may contribute for the reduction of disparities among cities.